The Role of Free Radicals and Antioxidant in Abortion - Aloysius Suryawan; Theresia Monica Rahardjo (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Free radicals and antioxidant exist in balance under normal condition. In prooxidant condition, excessive free radicals can initiate a state of oxidative stress (OS) followed by capillary endothelial cell damage, a process involved in the pathophysiology of abortion.CONTENT: Abortion is a common complication of pregnancy and occurs in 25% of women. Many factors can cause abortion including fetal factor, implantation process and hormonal status. Combination those factors with OS influence the entire reproductive life of a woman. Antioxidant can neutralize free radicals and used to reduce OS especially in recurrent abortion.SUMMARY: Antioxidant therapy is a very interesting field in abortion especially used as prevention approach mainly caused by the high cost of infertility treatment methods.KEYWORDS: free radical, antioxidant, abortion